Generational attitude differences : influences on organisational justice perceptions and resulting work outcomes - Lee, Pei Ying (Nanyang Technological University, 2020)
As Baby Boomer workers gradually move into retirement, Generation Y workers begin stepping into the workforce. As a result, the bulk of the labour force is now formed by Generation X and Generation Y workers (Department of Statistics Singapore, 2019). With this shift, employers are reporting difficulties and challenges in managing the new Generation Y workers (Erickson, 2009). To manage these challenges, this study investigates the generational differences in attitude, perception and reaction in the workplace. It theorised that Generation X and Generation Y differ on their need for validation and need for validation would moderate relationships of organizational justice perception as well as its resulting work outcomes. This study employed an experimental research design with the use of vignettes and self-reported measures, and the results were analysed using multiple regression. As expected, Generation Y had higher need for validation as compared to Generation X. Furthermore, need for validation was found to significantly moderate the relationship between perceived interactional justice and job satisfaction, as well as significantly predict work outcomes of presenteeism, job satisfaction and intention to quit. In conclusion, this study found need for validation to be a significant variable explaining for generational differences observed in the workplace.